Jubilees as the Composition of One Author? - VanderKam, James C. 1946- (2014)
The essay evaluates three recent hypotheses about subsequent modifications to the original text of the Book of Jubilees: (1) addition of eschatological texts (C. Berner), (2) interpolation of a series of passages (J. Kugel), and (3) addition of legal sections to pre-existing rewritten stories and encasing both types of material in a chronological framework (M. Segal). All three hypotheses as formulated by these scholars are found to be unconvincing, although the third in a reformulated way provides a more defensible account of the evidence.\n4207 \n4207